(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
Spinelli’s notions of ’self’ and ’worlding’ are examined from the perspective of the operational psycho-phenomenological model of consciousness as delineated in the paper, Consciousness as Reflexive Shadow. It is argued that Spinelli’s model still allows for an ontologically neutral approach to unpacking ’self’ and ’other’ within the ’how’ of the operations of attention deployment.